2019
DOI: 10.1111/1365-2656.13049
|View full text |Cite
|
Sign up to set email alerts
|

Maternal age at birth shapes offspring life‐history trajectory across generations in long‐lived Asian elephants

Abstract: Advanced maternal age at birth can have pronounced consequences for offspring health, survival and reproduction. If carried over to the next generation, such fitness effects could have important implications for population dynamics and the evolution of ageing, but these remain poorly understood. While many laboratory studies have investigated maternal age effects, relatively few studies have been conducted in natural populations, and they usually only present a “snapshot” of an offspring's lifetime. In the pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
35
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 24 publications
(39 citation statements)
references
References 77 publications
(132 reference statements)
4
35
0
Order By: Relevance
“…Calves of older mothers could also be expected to show higher mortality for this reason, due to the senescence of older www.nature.com/scientificreports www.nature.com/scientificreports/ females 46 , however we found that calves born to older mothers experienced slightly higher mortality during specific taming ages, but this effect was not significant. This is consistent with recent findings in this population that maternal age does not necessarily dictate survival in the first five years, but rather their overall lifespan 47 .…”
Section: Discussionsupporting
confidence: 93%
“…Calves of older mothers could also be expected to show higher mortality for this reason, due to the senescence of older www.nature.com/scientificreports www.nature.com/scientificreports/ females 46 , however we found that calves born to older mothers experienced slightly higher mortality during specific taming ages, but this effect was not significant. This is consistent with recent findings in this population that maternal age does not necessarily dictate survival in the first five years, but rather their overall lifespan 47 .…”
Section: Discussionsupporting
confidence: 93%
“…diet, temperature, pathogen prevalence) on offspring performance has been described for a long time (Curley, Mashoodh, & Champagne, 2011;Mousseau, 1998) but an increasing number of studies have revealed that parental age can also negatively impact F I G U R E 2 Breeding rate according to individual's age offspring survival (Fox, Bush, & Wallin, 2003;Priest, Mackowiak, & Promislow, 2002) and reproduction (Bouwhuis, Charmantier, Verhulst, & Sheldon, 2010;Ducatez et al, 2012;Lippens, Faivre, Lechenault, & Sorci, 2017;Priest, Roach, & Galloway, 2008;Schroeder, Nakagawa, Rees, Mannarelli, & Burke, 2015). For instance, in Asian elephants (Elephas maximus), older mothers produce offspring with impaired survival (Reichert et al, 2019) and in the rotifers Brachionus manjavacas, maternal age negatively affects offspring survival and reproduction (e.g. egg quality) (Bock, Jarvis, Corey, Stone, & Gribble, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…To investigate how our two correlates of stress co-varied with between-and within-individual variation in body condition, body weight data (as a proxy for condition) from 2016 to 2018 was collected simultaneously with the blood and faecal sample collection using an Eziweigh 3000 ® scale, capable of weighing up to 9000 kg to the nearest 10 kg. To control the effect of age on elephant's size, and following previous work (e.g., [52,53]), we calculated and used standardised weights as dependent variables (on average two measurements per individual with a range of one to eight measurements per individual), so that we could measure the changes in body weight relative to the typical weight at a given age. These standardised weights were obtained by dividing an individual's measured weight by the predicted weight at that age, as obtained from von Bertalanffy growth curves from this population (presented in [53]).…”
Section: Body Weightmentioning
confidence: 99%